Multiple assessments to value wild animals in the analysis of human-wildlife relationships: a case study in the Dry Chaco of Córdoba, Argentina - Tamburini, Daniela; Zamudio, Fernando; Cáceres, Daniel (Ethnobiology and Conservation, 2021)
Because different perceptions of wildlife are usually involved in decision making processes on the use of environmental commons and in human choices, assigning an importance value to wildlife can be a relevant issue to discuss. We propose to broaden the concept of cultural value (CV) considering the trade-offs between the positive and negative Nature’s Contributions to People including trade-offs influenced by near-past contexts. In a rural community of the Dry Chaco and aiming at knowing the importance of wildlife in people´s lives, we conducted free listings and semi-structured interviews. We calculated the cognitive salience (S) and five CV indexes (differing from one another in the number and types of values); the number of citations of each ethnospecies was used as an estimator of the local knowledge on wildlife. Local inhabitants value wild species by considering the satisfaction of material needs, immaterial aspects, and/or the damages that certain species may cause to their own goods or commons. The ethnospecies most widely and frequently used with material purpose in the near past and at present, and those considered the most harmful, showed the highest salience values. The CV index that integrates both positive and negative assessments was positively correlated with cognitive salience; this relationship support the results showing that cognitive salience it is not only conditioned by positive assessments but as a variable that captures the multiple assessments of the fauna, including the negative ones.